Smart City Laguna (Ceará, Brasil): metamorfoses de um território - Abrão Beleza, Camila Lima (2025)
The small Smart City Laguna, located in the state of Ceará (Brazil), created in 2015 by a holding of foreign capital companies, has emerged as the “first social smart city” in the world. Promoted to serve a low-income public, the new city is composed of standardized single-family homes, social equipment, services, trades, and industries, surrounded by walls and a greenbelt, fueled by ICTs of all sorts. However, this work, through research in primary and secondary sources, reveals other facets of this private town. Through a broader temporal (history) and spatial (territory) view, this article reveals the reasons for the creation of such an urban center and its consequences.